The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1038/s41598-018-34290-1
|View full text |Cite
|
Sign up to set email alerts
|

A novel somatic mutation of SIN3A detected in breast cancer by whole-exome sequencing enhances cell proliferation through ERα expression

Abstract: Breast cancer is the most frequent tumor in women, and in nearly two-thirds of cases, the tumors express estrogen receptor α (ERα, encoded by ESR1). Here, we performed whole-exome sequencing of 16 breast cancer tissues classified according to ESR1 expression and 12 samples of whole blood, and detected 310 somatic mutations in cancer tissues with high levels of ESR1 expression. Of the somatic mutations validated by a different deep sequencer, a novel nonsense somatic mutation, c.2830 C>T; p.Gln944*, in transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Thus, our findings indicate that SIN3A and SIN3B have distinct nuclear localization signals. Consistently, it has recently been shown that nonsense mutations at residue 949 in SIN3A results in a truncated protein with cytoplasmic localization (40), suggesting that the NLS of SIN3A resides within its C-terminus and is distinct from SIN3B NLS. Additionally, SIN3A, unlike SIN3B_2, did not enrich KPNA2 KPNA3, KPNA4, or KPNB1 (Fig.…”
Section: Protein Domain Organization Is Partially Conserved Between Ssupporting
confidence: 55%
“…Thus, our findings indicate that SIN3A and SIN3B have distinct nuclear localization signals. Consistently, it has recently been shown that nonsense mutations at residue 949 in SIN3A results in a truncated protein with cytoplasmic localization (40), suggesting that the NLS of SIN3A resides within its C-terminus and is distinct from SIN3B NLS. Additionally, SIN3A, unlike SIN3B_2, did not enrich KPNA2 KPNA3, KPNA4, or KPNB1 (Fig.…”
Section: Protein Domain Organization Is Partially Conserved Between Ssupporting
confidence: 55%
“…Interestingly, a region within SIN3A that aligns with the SIN3B NLS does not appear to influence the nuclear localization of SIN3A. A recent report showed that a truncated form of SIN3A mislocalized within the cytoplasm ( 49 ). As this SIN3A variant resulted from a nonsense mutation at residue 944, the C terminus of SIN3A is likely critical for nuclear import.…”
Section: Discussionmentioning
confidence: 99%
“…Forty-eight hours after siRNA transfection, ESCs were treated with or without cAMP for 4 days. Total RNAs extracted from three samples (control siRNA with no treatment, control siRNA with cAMP treatment, and WT1 siRNA with cAMP treatment) were subjected to RNA-sequence analysis as reported previously ( 4 , 7 , 83 ). mRNA was purified with oligo dT beads (NEBNext Poly(A) mRNA magnet Isolation Module, New England Biolabs).…”
Section: Methodsmentioning
confidence: 99%